1996
DOI: 10.1128/mcb.16.2.564
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus-Encoded Histone H1-Like Proteins Are Associated with Kinetoplast DNA in the Trypanosomatid Crithidia fasciculata

Abstract: Kinetoplast DNA (kDNA), the mitochondrial DNA of trypanosomatids, consists of thousands of minicircles and 20 to 30 maxicircles catenated into a single large network and exists in the cell as a highly organized compact disc structure. To investigate the role of kinetoplast-associated proteins in organizing and condensing kDNA networks into this disc structure, we have cloned three genes encoding kinetoplast-associated proteins. The KAP2, KAP3, and KAP4 genes encode proteins p18, p17, and p16, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 34 publications
6
87
0
1
Order By: Relevance
“…Because of the importance of this result, we questioned whether there might be an undiscovered splice acceptor site 5Ј of the octamer sequence located distal to the single identified splice acceptor. The known splice acceptor site was identified in several independent cDNA clones earlier by RT-PCR (26). Similar experiments have shown that the KAP3-GFP chimeric RNA is also spliced at this site in several independent isolates (data not shown).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Because of the importance of this result, we questioned whether there might be an undiscovered splice acceptor site 5Ј of the octamer sequence located distal to the single identified splice acceptor. The known splice acceptor site was identified in several independent cDNA clones earlier by RT-PCR (26). Similar experiments have shown that the KAP3-GFP chimeric RNA is also spliced at this site in several independent isolates (data not shown).…”
Section: Resultssupporting
confidence: 65%
“…In the present work we have examined the sequence requirements for cycling of the C. fasciculata KAP3 gene, a gene encoding a histone H1-like protein associated with kinetoplast DNA (8,26). A plasmid construct containing the KAP3 gene with 5Ј and 3Ј flanking sequences was used to insert the green fluorescent protein (GFP) gene in frame within KAP3 for use as a sequence tag to permit easy discrimination of the expressed transcript from that of the chromosomal KAP3 mRNA during the cell cycle.…”
mentioning
confidence: 99%
“…The C. fasciculata ligase gene is clearly distinct from the C. fasciculata nuclear DNA ligase I described (36) and also is unrelated to the mitochondrial DNA ligases (LIG III) of higher eukaryotes. However, the predicted N-terminal sequence of the kinetoplast ligase is consistent with the 9-aa cleavable sequences of several other kinetoplast-targeted proteins in C. fasciculata (37). Interestingly, the C. fasciculata nuclear LIG I gene is highly similar to LIG I genes of higher eukaryotes.…”
Section: Resultssupporting
confidence: 64%
“…H1299 cells (human lung large cell carcinoma) were purchased from ATCC. Anti-PIAS1 antibody was produced by immunizing New Zealand White rabbits with GST-PIAS1 (residues 47-180) as described previously (12). Other antibodies used were antip21 antibody (Upstate Biotechnology), anti-p53 DO-1 (Santa Cruz Biotechnology), anti-Flag (M2), and anti-actin antibodies (Sigma).…”
Section: Methodsmentioning
confidence: 99%